Lembar Kerja Peserta Didik pada Proyek Kapal Selam Sederhana Berbasis STEM-PJBL: Meningkatkan Pemahaman Konseptual tentang Prinsip Archimedes dalam Kondisi Keterbatasan Laboratorium - Dinar Maftukh Fajar; Irsyadul Ibad; Joko Suroso (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop and evaluate the feasibility of a Student Worksheet (LKPD) based on the STEM (Science, Technology, Engineering, and Mathematics) approach and the Project-Based Learning (PJBL) model through a simple submarine project, designed to enhance students’ conceptual understanding of Archimedes’ Principle in junior high schools with limited laboratory facilities. The LKPD was developed using the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. The product was validated by subject matter and media experts and its practicality was tested by a science teacher and students. Implementation involved 27 eighth-grade students and was evaluated using pretest and posttest instruments based on seven indicators of conceptual understanding. Validation results indicated that the LKPD was highly valid (scores of 4.80 and 4.20), practical (score of 4.60), and well-received by students. Classroom implementation showed high student engagement, with an interest score of 4.89. The average N-Gain of 0.47 reflected moderate effectiveness, with greater improvements in higher-order indicators such as classification, interpretation, and application. The use of simple, readily available materials allowed experimental activities despite limited resourses. Overall, the LKPD is feasible as a project-based learning tool and highlights the need to strengthen foundational concepts early in instruction.